PERSONALITY DEVELOPMENT OF THE CHARACTERS IN RATATOUILLE MOVIE 2007 - Fajar, Rahmat; Melati, Rima (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This study undertakes a qualitative exploration of the principal characters' personality traits within the 2007 film Ratatouille. Specifically, it aims to delineate the primary character's personality profile and to identify the salient factors influencing the personality development of these central figures. Employing a qualitative descriptive methodology, primary data was derived from the film itself, focusing on the personalities of the main characters. Data analysis adhered to the framework proposed by Miles and Huberman. Findings indicate that the character of Linguini exhibits a constellation of personality traits including insecurity, shyness, timidity, and introversion. In contrast, Skinner is characterized by anger and ambition. Several factors contributed to the personality development of both Linguini and Skinner. Linguini's personality trajectory, marked by a transition from insecurity to confidence, is attributable to environmental and learning factors. Skinner, initially driven by anger and ambition, undergoes a transformation toward greed and vengefulness as a result of environmental pressures and unconscious motivations, ultimately culminating in a desire to usurp control of the restaurant